Psychopathologic symptoms in post-myocardial infarction patients - Olajossy, Marcin; Koprianiuk, Agata (Current Problems of Psychiatry, 2011)
The study aimed to assess severity/features of psychopathologic symptoms in post-myocardial infarction patients in comparison to clinically healthy people.Study group and methods: Research was conducted in a group of 60 people. Clinical group included 30 patients (60% of males and 40% of females) after first myocardial infarction and 30 healthy people (control group). All the patients were assessed using sociodemographic questionnaire worked out by the authors and Hopkins Symptom Checklist (HSCL).Results and conclusions: Based on obtained results the following conclusions were made: 1. Patients after myocardial infarction showed higher results in all scales contained in HSCL Questionnaire in comparison to healthy people. 2. Depression is the dominating psychopathological symptom in post-myocardial infarction patients.